Factors affecting the ability of sustainable poverty reduction in U Minh district, Ca Mau province - Lê, Điền Nghi; Nguyễn, Quyết Thắng (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The artical "Factors affecting the ability of sustainable poverty reduction in U Minh district, Ca Mau province" was carried out to assess poverty reduction in the locality, thereby finding the factors affecting the ability to reduce poverty in the locality. sustainable poverty reduction. The study studied 10 factors affecting poverty and the remaining factors were not statistically significant. The study showed that the factors (1) education level of the household head, (2) average production area/per capita, (3) income per capita from nonagricultural activities have positively affect the ability to escape poverty. But factor (4) the number of dependents in the household has a negative impact on the ability to escape poverty. From the factors affecting the ability to escape from poverty, the author has proposed four main implications for implementing poverty reduction more sustainably in the coming time.